2021
DOI: 10.1371/journal.pone.0251391
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pilates and Yoga to improve bone density in adult women: A systematic review and meta-analysis

Abstract: Background The ageing population brings about the appearance of age-related health disorders, such as osteoporosis or osteopenia. These disorders are associated with fragility fractures. The impact is greater among postmenopausal women due to an acceleration of bone mineral density (BMD) loss. Objective To estimate the effectiveness of Pilates or Yoga on BMD in adult women. Methods Five electronics databases were searched up to April 2021. Randomized controlled trials (RCTs), non-RCTs and pre-post studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…As a form of exercise, the practice of yoga has increased rapidly in recent years among all age groups, as individuals seek ways to stay healthy and resolve physiological and psychological problems. The benefits of yoga practice have been demonstrated in previous studies: yoga improves flexibility and strength [1][2][3][4], raises the quality of life, reduces the risk of cardiovascular disease [5], and improves musculoskeletal health [6][7][8][9][10]. It has been reported that yoga is safe as a usual form of care and exercise [11].…”
Section: Introductionmentioning
confidence: 99%
“…As a form of exercise, the practice of yoga has increased rapidly in recent years among all age groups, as individuals seek ways to stay healthy and resolve physiological and psychological problems. The benefits of yoga practice have been demonstrated in previous studies: yoga improves flexibility and strength [1][2][3][4], raises the quality of life, reduces the risk of cardiovascular disease [5], and improves musculoskeletal health [6][7][8][9][10]. It has been reported that yoga is safe as a usual form of care and exercise [11].…”
Section: Introductionmentioning
confidence: 99%
“…As these patients are also prone to a higher fall risk, it is imperative that bone health be maintained from an early age. Yoga therapy has been shown to help maintain stability of bone mineral density in post-menopausal women, effectively preventing decline in bone strength [43]. Furthermore, yoga therapy has been shown to decrease pain levels and improve patient functioning which can improve mobility in these patients [36].…”
Section: Stability Of Bone Loss and Fracture Riskmentioning
confidence: 99%
“…Joseph Pilates developed Pilates using six key principles: centering, concentration, control, precision, flow, and breath [ 1 4 ] . Pilates training (PT) is intended to improve general body flexibility and health by emphasizing core strength, posture, and coordination of breathing with movement [ 4 , 5 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Joseph Pilates developed Pilates using six key principles: centering, concentration, control, precision, flow, and breath [ 1 4 ] . Pilates training (PT) is intended to improve general body flexibility and health by emphasizing core strength, posture, and coordination of breathing with movement [ 4 , 5 ] . Otherwise, PT has been used to reduce pain and disability [ 6 ] , to improve sports performance [ 2 , 4 ] , and to treat arterial-hypertension, chronic neck pain, and post-menopausal osteoporosis [ 6 ] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation